Localized nicardipine release implants for prevention of vasospasm after aneurysmal subarachnoid hemorrhage: a randomized clinical trial - Wessels, Lars; Wolf, Stefan; Adage, Tiziana; Breitenbach, Jörg; Thomé, Claudius; Kerschbaumer, Johannes; Bendszus, Martin; Gmeiner, Matthias; Gruber, Andreas; Wachter, Dorothee; Rohde, Veit; Wostrack, Maria; et al. (JAMA neurology, 2024)
Cerebral vasospasm largely contributes to a devastating outcome after aneurysmal subarachnoid hemorrhage (aSAH), with limited therapeutic options.To investigate the safety and efficacy of localized nicardipine release implants positioned around the basal cerebral vasculature at risk for developing proximal vasospasm after aSAH.This single-masked randomized clinical trial with a 52-week follow-up was performed between April 5, 2020, and January 23, 2023, at 6 academic neurovascular centers in Germany and Austria. Consecutive patients with World Federation of Neurological Surgeons grade 3 or 4 aSAH due to a ruptured anterior circulation aneurysm requiring microsurgical aneurysm repair participated.During aneurysm repair, patients were randomized 1:1 to intraoperatively receive 10 implants at 4 mg of nicardipine each plus standard of care (implant group) or aneurysm repair alone plus standard of care (control group).The primary end point was the incidence of moderate to severe cerebral angiographic vasospasm (aVS) between days 7 and 9 after aneurysm rupture as determined by digital subtraction angiography.Of 41 patients, 20 were randomized to the control group (mean [SD] age, 54.9 [9.1] years; 17 female [85%]) and 21 to the implant group (mean [SD] age, 53.6 [11.9] years; 14 female [67%]). A total of 39 patients were included in the primary efficacy analysis. In the control group, 11 of 19 patients (58%) developed moderate or severe aVS compared with 4 of 20 patients (20%) in the implant group (P = .02). This outcome was paralleled by a lower clinical need for vasospasm rescue therapy in the implant group (2 of 20 patients [10%]) compared with the control group (11 of 19 patients [58%]; P = .002). Between days 13 and 15 after aneurysm rupture, new cerebral infarcts were noted in 6 of 19 patients (32%) in the control group and in 2 of 20 patients (10%) in the implant group (P = .13). At 52 weeks, favorable outcomes were noted in 12 of 18 patients (67%) in the control group and 16 of 19 patients (84%) in the implant group (P = .27). The adverse event rate did not differ between groups.These findings show that placing nicardipine release implants during microsurgical aneurysm repair can provide safe and effective prevention of moderate to severe aVS after aSAH. A phase 3 clinical trial to investigate the effect of nicardipine implants on clinical outcome may be warranted.ClinicalTrials.gov Identifier: NCT04269408
Online veröffentlicht: 19. August 2024, korrigiert: 16. September 2024
Gesehen am 07.11.2024